Quantitative magnetic resonance imaging and the electrophysiology of the carpal tunnel region in floor cleaners - Pierre-Jerome, C.; Bekkelund, S. I.; Mellgren, S. I.; Torbergsen, T. (Scandinavian Journal of Work, Environment & Health, 1996)
' ' OBJECTIVES ': 'The purpose of this study was to evaluate possible structural changes of the wrist and subclinical damage in the median nerves of healthy floor cleaners.' ' METHODS ': 'Twenty-four cleaners and 19 referents (noncleaners), all women, underwent bilateral magnetic resonance (MR) wrist examination and nerve conduction studies. They were all randomly selected from an occupational health service. From MR images the volumes of the wrist, carpal tunnel, and thenar and hypothenar muscles were calculated, as well as the signal intensity of the median nerve, bilaterally.' ' RESULTS ': 'No significant difference in the volume of the carpal tunnel was found in the two groups. The relative signal intensity of the median nerve was 0.55 for the cleaners and 0.48 for the referents (P=0.05). The mean nerve conduction velocity values were 55.2 m/s for the right median nerve of the cleaners and 57.4 m/s for the right median nerve of the referents (P=0.03). The median nerve of the cleaners had a mean sensory amplitude of 128.2 bdV compared with 162.8 bdV for the referents (P=0.01). There was a tendency towards a longer distal latency of the median nerve in the cleaner group.' ' CONCLUSION ': 'This study revealed subclinical intrinsic damages to the median nerve, as demonstrated by MR, and poorer electrophysiological nerve functions among workers at high risk (cleaners) compared with workers at lower risk (noncleaners).
Keywords: floor cleaners; handworker; neurophysiology